2019
DOI: 10.1111/add.14768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of psychiatric comorbidity in treatment‐seeking, opioid‐dependent patients with versus without chronic pain

Abstract: Aim To compare psychiatric morbidity in treatment-seeking, opioid-dependent patients with versus without chronic pain. Design A retrospective comparative cohort design was used involving record linkage from routinely collected, nationally held data sets. Data were managed within a Scottish Government-certified Safe Haven. Setting and participants Participants comprised all patients of an NHS Substance Misuse Service in the East of Scotland (n = 467) who were in treatment during 2005 and had been in treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Catastrophizing is a negative cognitive-emotional process that includes components of magnification, helplessness, and rumination. The degree of catastrophizing is one of the most important predictors of pain treatment outcomes and a key variable in behavioral cognition approaches and fear-avoidance model (8). An individual's attitudes and beliefs, as well as sources and methods of coping with the pain, affect how s/he reports pain (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catastrophizing is a negative cognitive-emotional process that includes components of magnification, helplessness, and rumination. The degree of catastrophizing is one of the most important predictors of pain treatment outcomes and a key variable in behavioral cognition approaches and fear-avoidance model (8). An individual's attitudes and beliefs, as well as sources and methods of coping with the pain, affect how s/he reports pain (9).…”
Section: Introductionmentioning
confidence: 99%
“…The most important effect of catastrophizing on chronic pain is that patients with pain receive an assessment of pain that may make them more alert to painful or threatening feelings and fear of experiencing painful feelings in the future (10). psychological symptoms that can contribute to the development of chronic pain, the persistence of pain symptoms, and response to medical treatment (8). Studies have shown that psychological variables such as attitudes, anxiety, and depression, instead of biomedical factors, should be considered both physically and psychologically.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that opioid-dependent patients with comorbid CP present with relatively more complex medical and psychiatric complications than those without pain -indeed our previous work has shown this in relation to psychiatric disorders. 18 Future research studies might consider including a third, comparator group -those with opioid use problems and no pain problems. This is the first study to examine both the patientattributed causal direction of ODD and CP and its association with health and clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…17 The present study used the 12-month threshold since, in a clinical population familiar with persistent, debilitating conditions, this was considered as the best indication of truly ‘chronic’ pain, an approach that has been used in other studies. 4 , 18 Those that reported having had pain for less than 12 months were excluded from the study since they were considered to form a small, relatively heterogeneous group. No participants were lost during the course of the study: as discussed below, since only anonymised data were used, participants were not required to consent to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Higgins et al . present a case–control study of psychiatric morbidity in Scottish National Health Service patients with and without chronic pain presenting for methadone treatment of opioid dependence . They find that the patients with chronic pain score consistently higher on self‐report measures of psychopathology and receive more psychotropic medications.…”
mentioning
confidence: 96%